(untitled) (Window of Public Health Journal, 2026)
Hypercholesterolemia contributes to an increased risk of cardiovascular disease and stroke. In Indonesia, cardiovascular diseases account for approximately 30% of total deaths1. One of the non-pharmacological therapies to prevent high cholesterol is engaging in regular physical activity, such as aerobic exercise2. Aerobic exercise is proven to be an effective form of physical activity that enhances cardiovascular and pulmonary fitness while lowering total blood cholesterol levels3. This study aimed to determine the effect of aerobic exercise on the reduction of total cholesterol levels among the community in the working area of Kassi Kassi Public Health Center, Makassar City. This research employed a quantitative approach with a true experimental design using a Pretest-Posttest with Control Group model. The study population comprised residents within the health center’s working area, and the sample consisted of 15 respondents selected through purposive sampling. The intervention involved six aerobic exercise sessions conducted over 14 days. Total cholesterol levels were measured before and after the intervention, followed by data normality testing and analysis using the Wilcoxon test. The results showed a significant decrease in total cholesterol levels after the intervention (p-value = 0.001 < 0.05). Based on these findings, it can be concluded that aerobic exercise has a positive impact on lowering total cholesterol levels. Aerobic exercise is expected to serve as an effective, low-cost, and accessible non-pharmacological strategy for preventing non-communicable diseases associated with high cholesterol.